Testing of a Solar-PV/Wind operated AC-DC Microgrid with LabVIEW Controller - Vinu Thomas; Sivaprasad Athikkal; Kumaravel Sundaramoorthy; Ashok Sankar (Institute of Advanced Engineering and Science, 2018)
This paper discusses about a LabVIEW based controller for the hybrid renewable energy system operated AC-DC microgrid with the major objectives of: i) predicting the power generation potential of the solar–PV and wind generators ii) effective power management iii) load scheduling based on the available power with the renewable sources and iv) grid/islanding mode of operation of the microgrid. In order topredict the output power of wind generator and Solar-PV system, an artificial neural network is developed.The laboratory-scale model of three phase, 400 V, 10 kVA microgrid structure is developed at National Institute of Technology Calicut, India. The developed LabVIEW based controller has been tested successfully for a real-time load and source in the laboratory environment. Test results show that the designed controller is effectively managing the output powerof the primary energy sources under different scenarios.